Handbook of research on cybersecurity issues and challenges for business and FinTech applications - Saeed, Saqib 1970-; Almuhaideb, Abdullah M.; Kumar, Neeraj; Zaman, Noor 1972-; Zikria, Yousaf Bin (IGI Global, 2023)
This book offers high-quality original research contributions on the specialized theme of cybersecurity challenges in diverse business areas, disseminating theoretical foundations and empirical studies by researchers and practitioners to realize dependable technological systems.